PENGUATAN PENDIDIKAN KARAKTER BERBASIS BUDAYA ORGANISASI DI SDIT AL MADANI TAPIN - Sulaiman Jazuli (Atta'dib Jurnal Pendidikan Agama Islam, 2022)
This study aims to determine the process of strengthening the character Education-based culture of the organization in SDIT Al Madani Tapin. This type of research is qualitative with the approach of narrative analysis. Instruments and data collection Techniques by observation, interview, and documentation. The results of the research show that the main character-based culture of the organization in SDIT Al Madani Tapin is self-help, moral qurani, competitive, and environmentally sound. While in the strengthening of character education based on the culture of the organization, SDIT Al Madani used procurement strategy school parents, in collaboration with the parents in monitoring the behavior of the learners, and held a market class once a year. The method used is the method of habituation, the method of reward and punishment, and methods example. The Media used is the star of the class, diary shalih-shalihah, and the applicable rules at school. Whereas in providing evaluation, SDIT Al Madani performs the assessment of daily academic, and character assessment of learners. Keywords: Reinforcement, Character Education, Culture-Based Organizations